The Wildlife Docusoap: A New Ethical Practice for Wildlife Documentary?. (May 2014) - Richards, Morgan
This article explores the ethical implications of the rise of a new style of personality presenter-led wildlife programming in the 1990s, reliant, in part, on digital video and aimed at creating a sense of "liveness." It takes the BBC series Big Cat Diary (1996) as its focus, looking at how the BBC responded to increased market pressure by creating the first wildlife docusoap. Despite the lightweight connotations of the docusoap format, this series put forward a new ethical practice for representing the lives of individual wild animals. Through an exploration of how ethics are implicated in changing conditions of production and evolving media technologies, it is proposed that debates about the ethics of wildlife documentary need to be recentered on the complex ethical relationships between wildlife documentary makers and the animals and ecosystems they film rather than on issues of audience deception.